'Atypical' CAR T cells: NKG2D and Erb-B as examples of natural receptor/ligands to target recalcitrant solid tumors. (August 2017) - Gilham, David E; Maher, John
Chimeric antigen receptor (CAR) T-cell therapy has recently been recommended for approval for certain B-cell malignancies bringing the approach closer to mainstream cancer treatment. This rapid rise to prominence has been driven by impressive clinical results and the means to successfully commercialize the approach now being actively pursued. The current success of CAR T cells in B-cell malignancies relies upon the absolute lineage specificity of the CD19 antigen. CARs can also be targeted using non-antibody approaches, including the use of receptors and ligands to provide target specificity that have different specificities and binding kinetics. The specific examples of NKG2D and Erb-B are used that provide different characteristics and target profiles for CAR T-cell therapy of cancer.